2012
DOI: 10.1002/cbdv.201100208
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids in Subtribe Centaureinae (Cass.)Dumort.(Tribe Cardueae, Asteraceae): Distribution and13C‐NMR Spectral Data

Abstract: This review reports the occurrence of flavonoids in subtribe Centaureinae of Asteraceae family. It extensively covers the literature up to 2010 and collects all available (13)C-NMR data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 209 publications
(26 reference statements)
0
26
0
Order By: Relevance
“…Centaurea species have been the object of various phytochemical studies, with a diversity of bioactive phytochemicals and prevalence of flavonoids 2 , flavonoid aglycones 3 , lignans 4 , sesquiterpene lactones 5 , essential oils 6 , alkaloids 7 and other biologically active constituents. Some species of the genus Centaurea have been used as medicinal plants in folk medicine for their uses in gastrointestinal 8 and inflammatory disorders 9 , cytotoxic activity 4,10 , in addition to the anti-microbial 11,12 and antioxidant activities 13 .…”
Section: Genusmentioning
confidence: 99%
“…Centaurea species have been the object of various phytochemical studies, with a diversity of bioactive phytochemicals and prevalence of flavonoids 2 , flavonoid aglycones 3 , lignans 4 , sesquiterpene lactones 5 , essential oils 6 , alkaloids 7 and other biologically active constituents. Some species of the genus Centaurea have been used as medicinal plants in folk medicine for their uses in gastrointestinal 8 and inflammatory disorders 9 , cytotoxic activity 4,10 , in addition to the anti-microbial 11,12 and antioxidant activities 13 .…”
Section: Genusmentioning
confidence: 99%
“…C. calcitrapa is used in traditional medicine as antidiabetic and diuretic [3,4]. Several previous chemical studies have been reported on the genus [5][6][7][8][9].…”
mentioning
confidence: 99%
“…C. calcitrapa is used in traditional medicine as antidiabetic and diuretic [3,4]. Several previous chemical studies have been reported on the genus [5][6][7][8][9].Continuing our research on the chemical constituents of Algerian Centaurea species [10-16], we report here the isolation of six flavonoids and a sesquiterpene lactone, cnicin, from the chloroform exudate of the aerial parts of Centaurea calcitrapa L.Fresh aerial parts (1.8 kg) were extracted with a mixture of toluene-ethyl acetate (6:4) twice during 15 min. The obtained solutions were combined and concentrated.…”
mentioning
confidence: 99%
“…Many members of this genus are used in traditional folk medicine, such as Centaurea pulchella used to treat skin problems such as to resolve the abscess [4a]. Although biological activity of many Centaurea species have been investigated in different countries and Turkey [3][4][5][6][7][8], cytotoxic effect of C. patula, C. pulchella and C. tchihatcheffii has not been studied yet.…”
mentioning
confidence: 99%